METHODOLOGICAL BASIS OF ANALYSIS OF WORKS OF MEDIA CULTURE - Kh.Kh. Nekboyev (American Journals, 2023)
This article talks about the methodological foundations of the analysis of media culture works.
Keywords: Media education, media education models, media education practice, media materials, information technologies.